Atomistic Simulations of the Reactivity of Acanthite Facets toward Cyanidation - Soto F.A. (2019)
Cyanidation (leaching with cyanide) is a common yet complex surface process in hydrometallurgical practice, and its effectiveness in extracting the metal of interest is often affected by the nature of the mineralogical species that are present. Little is known about surface processes on acanthite (a silver sulfide) and how its various facets respond to cyanidation in aqueous solution. Therefore, in this work, some properties of both bulk acanthite (Ag2S) and its (001), (022), and (1̅21) surface facets have been studied by density-functional-theory (DFT)-based calculations to elucidate reactivity trends and competitive adsorption (initial stages in the surface process of cyanidation) between cyanide and other species present in the leaching liquor. It is found that CN– binds by its C-end to silver sites on the acanthite surface with adsorption energy similar to that of OH– but stronger than those of water and oxygen. Ab initio molecular dynamics (AIMD) simulation of cyanidation liquor over acanthite surfaces reveals the presence of a precursor for the dicyanoargentate complex for the (022) facet but not for the (001) and (1̅21) facets. This suggests a higher reactivity of the (022) facet toward the adsorption of cyanidation species than those of the (001) and (1̅21) facets. Although from the three facets investigated, the (022) facet is found to be the least stable according to surface energy calculations in a vacuum, the facet is detected experimentally during the synthesis of acanthite powders. Thus, given the much stronger adsorption of CN– ions in solution identified by the DFT and AIMD studies, the most reactive (022) facet may be stabilized by the adsorbates.